Implementation of a new flux rotor based on model reference adaptive system for sensorless direct torque control modified for induction motor - Saifi, R. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Introduction. In order to realize an efficient speed control of induction motor, speed sensors, such as encoder, resolver or tachometer may be utilized. However, some problems appear such as, need of shaft extension, which decreases the mechanical robustness of the drive, reduce the reliability, and increase in cost. Purpose. In order to eliminate of speed sensors without losing. Several solutions to solve this problem have been suggested. Based on the motor fundamental excitation model, high frequency signal injection methods. The necessity of external hardware for signal injection and the adverse influence of injecting signal on the motor performance do not constitute an advantage for this technique. Fundamental model-based strategies method using instantaneous values of stator voltages and currents to estimate the rotor speed has been investigate. Several other methods have been proposed, such as model reference adaptive system, sliding mode observers, Luenberger observer and Kalman filter. The novelty of the proposed work consists in presenting a model reference adaptive system based speed estimator for sensorless direct torque control modified for induction motor drive. The model reference adaptive system is formed with flux rotor and the estimated stator current vector. Methods. The reference model utilizes measured current vector. On the other hand, the adjustable model uses the estimated stator current vector. The current is estimated through the solution of machine state equations. Practical value. The merits of the proposed estimator are demonstrated experimentally through a test-rig realized via the dSPACE DS1104 card in various operating conditions. The experimental results show the efficiency of the proposed speed estimation technique. Experimental results show the effectiveness of the proposed speed estimation method at nominal speed regions and speed reversal, and good results with respect to measurement speed estimation errors obtained.

Вступ. Щоб реалізувати ефективне керування швидкістю асинхронного двигуна, можна використовувати датчики швидкості, такі як енкодер, резольвер або тахометр. Однак виникають деякі проблеми, такі як необхідність подовження валу, що знижує механічну міцність приводу, знижує надійність та збільшує вартість. Мета. Для усунення датчиків швидкості без втрати. Було запропоновано кілька рішень на вирішення цієї проблеми. На основі моделі основного порушення двигуна використовуються методи подачі високочастотного сигналу. Необхідність зовнішнього обладнання для подачі сигналу та несприятливий вплив подачі сигналу на роботу двигуна не є перевагою цього методу. Досліджено метод стратегій на основі фундаментальних моделей з використанням миттєвих значень напруг та струмів статора для оцінки швидкості обертання ротора. Було запропоновано кілька інших методів, таких як еталонна адаптивна система моделі, спостерігачі режиму ковзання, спостерігач Люенбергера і фільтр Калмана. Новизна запропонованої роботи полягає у поданні модельної еталонної адаптивної системи оцінки швидкості прямого бездатчикового управління моментом, модифікованої для асинхронного електроприводу. Еталонна адаптивна система моделі формується з магнітним потоком ротора та оціненим вектором струму статора. Методи. Еталонна модель використовує вимірюваний вектор струму. З іншого боку, модель, що регулюється, використовує передбачуваний вектор струму статора. Струм оцінюється шляхом вирішення рівнянь стану машини. Практична цінність. Переваги запропонованого оцінювача продемонстровані експериментально на тестовій установці, реалізованій на платі dSPACE DS1104 у різних умовах експлуатації. Експериментальні результати свідчать про ефективність запропонованої методики оцінки швидкості. Експериментальні результати показують ефективність запропонованого методу оцінки швидкості в областях номінальних швидкостей та реверсивних швидкостей, а також хороші результати щодо отриманих похибок оцінки швидкості вимірювання.
Keywords: induction motor; model reference adaptive system; sensorless speed; direct torque control; асинхронний двигун; еталонна адаптивна система; бездатчикова швидкість; пряме управління крутним моментом